Development of composite risk index for federal roads in Malaysia - Intan Suhana, Mohd Razelan (2015)
According to WHO (2013), middle-income countries like Malaysia, Indonesia and several other ASEAN countries suffer the highest traffic fatality rates compared to most developed countries where crash statistics are used to evaluate the safety status of these countries. Crash data has been acknowledged as the most popular and acceptable road safety indicator in recognizing road section's safety status. However, the reliability of crash data in correctly identifying the road section's safety status has been widely argued by road safety experts. In light of that, a new method called composite risk index that would act as a proactive measure in evaluating road section's safety status has been introduced and tested in this research. This research attempts to fill in the missing links on the role of different road environment factors in producing risk towards road users. Other than that, a significant contribution to the knowledge in the theory of road safety index is made by developing a risk index in evaluating road section's safety status. Identifications of the road environment factors of the existing road networks were done by adopting naturalistic driving method in recording different road environment conditions for 315.5 km length of federal road. The road environment factors for the whole study area were identified by clustering fourteen original attributes into several groups having similar characteristics.